Journal of Religious Education - Goldburg, Peta.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer.)
Journal of Religious Education is a refereed publication for the academic exploration of the task of religious education in modern society. The journal helps disseminate original writings and research in religious education and catechesis - particularly as it relates to the faith formation of children and young people. Articles for publication on religious education in various contexts and on related areas, as well as book reviews are welcome.
Keywords: Religion; Church and education; Religion and Education; Religious Studies, general